Peran Pasar Modal Syariah Dalam Mendorong Laju Pertumbuhan Ekonomi Di Indonesia - M Fauzan; Dedi Suhendro (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2018)
This study has a long-term goal that is to see how big the role of sharia capital market in encouraging the rate of economic growth in Indonesia. This research has benefits to the Government, investors and all stakeholders for the development of shariah financial industry especially Sharia Capital Market in Indonesia. The method to be used in this research is data collection, literature study related to this research, problem identification, pre-process, data analysis, data analysis result and final evaluation from result of data processing. Sharia capital market instruments are sharia, syariah (sukuk) and shariah mutual funds. The data used is the Financial Services Authority data through the website www.ojk.go.id and data Central Bureau of Statistics through the website www.bps.go.id. The development of capital market in Indonesia, which is reflected in the main indicators of capital market that continues to grow from year to year can be a driver of economic growth by making investment activity began to increase. This increase is partly driven by the development of syariah capital market. The strong role of sharia capital market in the formation of the capital market capitalization of Indonesia (Composite Stock Price Index) indicates that sharia capital market has a big role in encouraging economic growth in Indonesia.